Waiting for the Unicorn Poems and Lyrics of China's Last Dynasty, 1644-1911 - Lo, Irving Yucheng; Schultz, William (Indiana University Press, 1986)
This is the first comprehensive English anthology of poetry from China's last great dynasty, the period 1644-1911. Waiting for the Unicorn is a direct descendant of Sunflower Splendor. After that seminal volume was published, it became clear that many scholars and students wanted more detailed coverage of specific dynasties. The Ch'ing Dynasty was the obvious place to start. This volume presents the works of seventy-two individual poets from Sung Wan (1614-1673) to Ch'iu Chin (1877-1907) and Wang Kuo-wei (1877-1927). Over forty scholars in the United States and Canada have been working together with Professors Lo and Schultz for more than half a dozen years in the selection and preparation of these translations. Besides the translations themselves, there is a short bio-critical essay on each poet and an introduction by the editors.